THE ROLE AND SIGNIFICANCE OF MEDIATION AND ARBITRATION AS AN ALTERNATIVE METHOD OF DISPUTE RESOLUTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The concept of Alternative Dispute Resolution its essence is aspects of the advantage, Alternative Dispute Resolution features of the conflict, the concept of mediation and the essence is the basic principles of mediation, the concept of arbitration courts and essence, basic principles and functions of arbitration courts.